The Asian house shrew Suncus murinus as a reservoir and source of human outbreaks of plague in Madagascar. - Soanandrasana Rahelinirina; Minoarisoa Rajerison; Sandra Telfer; Cyril Savin; Elisabeth Carniel; Jean-Marc Duplantier (Public Library of Science (PLoS), 2017)
Identifying key reservoirs for zoonoses is crucial for understanding variation in incidence. Plague re-emerged in Mahajanga, Madagascar in the 1990s but there has been no confirmed case since 1999. Here we combine ecological and genetic data, from during and after the epidemics, with experimental infections to examine the role of the shrew Suncus murinus in the plague epidemiological cycle. The predominance of S. murinus captures during the epidemics, their carriage of the flea vector and their infection with Yersinia pestis suggest they played an important role in the maintenance and transmission of plague. S. murinus exhibit a high but variable resistance to experimental Y. pestis infections, providing evidence of its ability to act as a maintenance host. Genetic analyses of the strains isolated from various hosts were consistent with two partially-linked transmission cycles, with plague persisting within the S. murinus population, occasionally spilling over into the rat and human populations. The recent isolation from a rat in Mahajanga of a Y. pestis strain genetically close to shrew strains obtained during the epidemics reinforces this hypothesis and suggests circulation of plague continues. The observed decline in S. murinus and Xenopsylla cheopis since the epidemics appears to have decreased the frequency of spillover events to the more susceptible rats, which act as a source of infection for humans. Although this may explain the lack of confirmed human cases in recent years, the current circulation of plague within the city highlights the continuing health threat.